Study of moisture structurization and binding form changes in pectin gels by differential scanning calorimetry - Крапивницька, Ірина Олексіївна; Потапов, Володимир Олексійович; Гурський, Петро Васильович; Перцевой, Федір Всеволодович (Eastern-European Journal of Enterprise Technologies, 2015)
During thermal cycling, changes in the structure and moisture-holding capacity of the samples of pectin gels with different formulations were investigated using differential scanning calorimetry by their cyclic heating and freezing. The fact that pectin gels are used for a wide variety of foods and semi-finished products, subjected to heat treatment in a wide temperature range from positive to negative was also taken into account during thermal cycling. The influence of the main formula components on the bound water volume increase, structure stability and gelation duration in pectin gels when heating and freezing was proved. Temperature ranges of phase transitions, which suggest that low-esterified pectin gels, containing sugar, citric acid and calcium citrate retain their structure and ensure the final quality of finished products, in which they are used were determined.